Gender, Fairy Tale, and Ecology in Sarah Orne Jewett’s A White Heron - Stephen Dougherty (Polilog: Studia Neofilologiczne)
This essay situates Sarah Orne Jewett’s short story A White Heron within the related contexts of children’s literature, the fairy tale, and crit ical ecofeminism, featuring comparative analysis of Jewett’s story and Angela Carter’s The Company of Wolves. Both stories are at least partly re-imaginings of Little Red Riding Hood, and both stories pursue what I identify as comparable ecofeminist or proto-ecofeminist agendas. While I argue it is Jewett’s shy and withdrawn protagonist Sylvia who is actually the more convincing ecofeminist warrior, and not Carter’s bold and aggressive heroine, it is only after Sylvia escapes from the story of Little Red Riding Hood that she becomes so; it is only after this intertextual dimension of A White Heron disappears from Jewett’s storytelling that Sylvia assumes an ecofeminist mantle, and a decisively moral status.